2021
DOI: 10.1016/j.bpsgos.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Impact of Childhood Adversity on Early Adolescent Mental Health During the COVID-19 Pandemic in the ABCD Study Cohort: Does Race or Ethnicity Moderate Findings?

Abstract: Background During the COVID-19 pandemic in the United States, mental health among youth has been negatively impacted. Youth with a history of adverse childhood experiences (ACEs), as well as youth from minoritized racial-ethnic backgrounds, may be especially vulnerable to experiencing COVID-19-related distress. The current aims are to examine whether exposure to pre-pandemic ACEs predicts mental health during the COVID-19 pandemic in youth and whether racial-ethnic background moderated these effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 73 publications
2
33
0
Order By: Relevance
“…Due to the onset of the pandemic, several studies have indicated increases in mental health symptoms in children and adolescents in China, Western Europe, Canada, and the United States (5). For instance, school closures as a preventive action led to students struggling with unexpected disturbances in their daily routine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the onset of the pandemic, several studies have indicated increases in mental health symptoms in children and adolescents in China, Western Europe, Canada, and the United States (5). For instance, school closures as a preventive action led to students struggling with unexpected disturbances in their daily routine.…”
Section: Introductionmentioning
confidence: 99%
“…Low physical activity, anxiety and depression, fear of the uncertain future, poor interaction and parent-child conflicts, and increased sedentary behavior are all among the negative impacts of the COVID-19 pandemic on the mental health of children and consequently the family (6). According to this mental health crisis, the implementation of targeted intervention can be essential (5).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies examining the possible effect of ACEs on mental health during the pandemic have shown an association between ACEs and symptoms of depression, anxiety, and COVID-19-related stress and fear in both young adults 33 and adolescents. 34 , 35 Yet, the relationship between ACEs, COVID-19-related anxiety, and sleep quality remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest the impact and experience of the pandemic among youth may differ by sociodemographic factors such as sex and race/ethnicity. For example, one study in the same cohort found that female youth showed higher levels of psychological distress than males (Kiss et al., 2022 ), and another found youth from underrepresented racial and ethnic groups experienced greater socio‐emotional adversity during the pandemic (Stinson et al., 2021 ). Given that underrepresented racial and ethnic groups have been disproportionately impacted by COVID‐19‐related disruptions (Shim & Starks, 2021 ), family well‐being may also differ among groups more affected by the pandemic.…”
Section: Strengths and Limitationsmentioning
confidence: 99%